2015
DOI: 10.1002/jib.238
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR-based metabolomics approach for understanding the fermentation behaviour ofBacillus licheniformis

Abstract: *Bacillus licheniformis has been found to be one of the persistent dominant microorganisms in Daqu, which is a traditional fermentation starter, and it has been used to intensify certain strains. To understand the impact of B. licheniformis on Daqu, the fermentation behaviour of B. licheniformis was studied using 1 H NMR-based non-targeted analysis and principal component analysis. During the fermentation, 53 compounds were identified. Among them, seven compounds were largely consumed and 17 metabolites were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In our study, protease activities yielded positive correlations with alcohols (ethanol and glycerol in light‐flavour type Daqu ; ethylene glycol in strong‐flavour type Daqu ), amino acids (threonine in light type Daqu ; s‐sulfocysteine in strong‐flavour type Daqu ), organic acids (succinate in light‐flavour type Daqu ), sugars and sugar derivatives (galactitol in in light‐flavour type Daqu ; glucitol, lactose and mannitol in strong‐flavour type Daqu ; glucose in sauce‐flavour‐type Daqu ), secondary metabolites and vitamin (guanidoacetate in strong‐flavour‐type Daqu ; ascorbate in sauce‐flavour‐type Daqu ). Among others, alcohols can polymerise with organic acids to form esters, which are the main flavour compounds in baijiu such as ethyl acetate, ethyl propionate, ethyl lactate and ethyl caproate . The heatmap showed that protease activities could influence the alcohols and organic acids in different flavour type of Daqu significantly and differently.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, protease activities yielded positive correlations with alcohols (ethanol and glycerol in light‐flavour type Daqu ; ethylene glycol in strong‐flavour type Daqu ), amino acids (threonine in light type Daqu ; s‐sulfocysteine in strong‐flavour type Daqu ), organic acids (succinate in light‐flavour type Daqu ), sugars and sugar derivatives (galactitol in in light‐flavour type Daqu ; glucitol, lactose and mannitol in strong‐flavour type Daqu ; glucose in sauce‐flavour‐type Daqu ), secondary metabolites and vitamin (guanidoacetate in strong‐flavour‐type Daqu ; ascorbate in sauce‐flavour‐type Daqu ). Among others, alcohols can polymerise with organic acids to form esters, which are the main flavour compounds in baijiu such as ethyl acetate, ethyl propionate, ethyl lactate and ethyl caproate . The heatmap showed that protease activities could influence the alcohols and organic acids in different flavour type of Daqu significantly and differently.…”
Section: Resultsmentioning
confidence: 99%
“…1 H NMR spectra were obtained by a Avance III 600‐MHz NMR spectrometer (Bruker, Karlsruhe, Germany) operating at a proton NMR frequency of 600.13 MHz and a temperature of 300 K, using a 5 mm PATXI probe. For each sample, 128 scans were recorded, with the following parameters: pulse sequence, NOESYGPPR1D (RD–90°– t 1 –90°– t m –90°‐acquisition); relaxation delay, 2.00 s; mixing time (for NOESY), 1.00 s; acquisition time, 2.28 s; number of steady states transients (dummy scans), 4; gradient pulse times, 1 ms; solvent suppression, presaturation with spoil gradient; spectral width, 7184 Hz; time domain size, 32 k) …”
Section: Methodsmentioning
confidence: 99%
“…et al, 2015 ). B. licheniformis present in daqu were found to secrete amylase ( Li et al, 2014 ), protease, and some flavoring compound precursors ( Yan et al, 2015 ). A recent study showed that inoculation of B. licheniformis in daqu fermentation changed the entire microbial community structure and metabolic profile of daqu ( Wang P. et al, 2017 ).…”
Section: Microbial Diversity Revealed By Culture-independent Methodsmentioning
confidence: 99%
“…1 H-NMR spectra were obtained using an Avance 600-MHz NMR spectrometer (Bruker, Germany) operating at a proton NMR frequency of 600.13 MHz and a temperature of 300 K, using a 5 mm PATXI probe. For each sample, 128 scans were recorded, with the following parameters: pulse sequence, NOESYGPPR1D (RD-90°-t1-90°-tm-90°-acquisition); relaxation delay, 2.00 s; mixing time (for NOESY), 1.00 s; acquisition time, 2.28 s; number of steady-state transients (dummy scans), 4; gradient pulse times, 1 ms; solvent suppression, presaturation with spoil gradient; spectral width, 7184 Hz; time domain size, 32 k. [14] Metabolites were identified and quantified with Chenomx software (version 7.0; Chenomx Inc., Canada) with the reference of internal standard TSP. Each experiment was repeated three times.…”
Section: Analysis Of Nonvolatile Compounds Using 1 H-nmr Spectroscopy During Sufu Fermentationmentioning
confidence: 99%